Estimating nocturnal bird densities in oil palm agroecosystem based on distance sampling - Syed Hassan, Sharifah Nur Atikah (2017)
Nocturnal birds play important role in oil palm agroecosystem especially with respect to controlling pest populations. However, only Barn Owl has been widely studied in oil palm plantations while other nocturnal species remain understudied. The surveys were conducted on nocturnal birds (Strigiformes and Caprimulgiformes) in oil palm smallholdings at Tanjung Karang, Kuala Selangor, from May to October 2013. Nocturnal bird sampling was carried out between 2000 hr to 0100 hr across 80 survey points spaced at least 800 m apart. Bird calls were listened both before and after broadcasting a 1-min recording of call for each of the seven species recorded on-site. Environmental factors including; number of crop species and average height of oil palm stands; distances to the nearest forest, river and road; number of houses in 100m radius, oil palms and other crops; width of drain and road, were also measured at each point. The results showed that the most abundant species was Large-tailed Nightjar (Caprimulgus macrurus; 273 encounters, 47.31% from total of 577 recorded encounters; mean of 3.425), followed with Spotted Wood Owl (Strix seloputo; 152 encounters, 26.30%; mean: 1.9), Sunda Scops Owl (Otus lempiji; 101 encounters; 17.47%; mean: 1.263) and Common Barn Owl (Tyto alba; 34 encounters, 5.89%; mean: 0.425). One species associated with wildlife habitat was also recorded during the study, i.e. Brown Wood Owl (Strix leptogramica; 7 encounters). The results of Generalised Linear Models (GLMs) showed that two predictor variables (i.e. distance to the nearest river with slope estimate = 0.0828 and average height of oil palm stands with slope estimate = 0.0417) influenced the nocturnal bird richness while number of houses in 100m radius (slope estimate = 0.0487), number of oil palm stand (slope estimate = 0.0351), distance to forest (slope estimation = -0.1164) and distance to the nearest road (slope estimate = 0.0328) were found to influence the relative abundance of the nocturnal bird species in oil palm smallholdings. The presence of a high density of nocturnal birds in oil palm smallholdings may be associated with the availability of food resource and roosting structure as well as ecotone. The findings from this study suggest that maintaining certain habitat features while reducing human disturbances (such as houses and roads) may be beneficial to nocturnal bird species in the smallholdings.